The Fourth Stage: Wole Soyinka and the Social Character of Ibadan. - Ibironke, Olabode (History compass, 2015)
This article traces the origin and development of modern African literature in Ibadan, in the 1960s. It argues that Soyinka's famous concept, the Fourth Stage, is his attempt to capture the unique and transformative character of the city of Ibadan. A major portion of African literary history is mostly available through writers' autobiographies such as Soyinka's Ibadan. This article promotes the idea of reading more of these autobiographies as literary history in order to recover the specificity and spirit of African literary production. Indeed, the ways in which the founding texts of African literature are reflective of the social character of the city might be lost if the history of local publication is not resurrected. By locating the origins of the idea of the Fourth Stage in Ibadan, I set the stage for the sequel to this paper that argues that although the African Writers Series published by Heinemann Educational Books canonized African literature, the process of that canonization was already well underway through Mbari publication that was located in Ibadan. Taken together, these two articles underscore the significance of Mbari publication as the outcome of literary activities centered on the Mbari literary club in the heart of Ibadan; the club and the publication were unique to the social character of the city as such.